2011
DOI: 10.1002/hlca.201100111
|View full text |Cite
|
Sign up to set email alerts
|

Two New Meroterpenes from the Mangrove Endophytic Fungus Aspergillus sp. 085241B

Abstract: Two new meroterpenes, acetoxydehydroaustin B (1) and 1,2-dihydro-acetoxydehydroaustin B (2) were isolated in the form of a mixed crystal from the mangrove endophytic fungus Aspergillus sp. 085241B. Their structures and absolute configurations were determined by extensive analysis of their spectra and X-ray diffraction data. In a preliminary bioassay, the mixed crystal did not exhibit activities against cancer cell lines of MDA-MB-435, SKBR3, HepG2, HEP3B, PC-3, and A549, as well as against aglucosidase and tyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In continuing the search for novel and bioactive natural products from mangrove endophytic fungi [ 17 , 18 , 19 , 20 ], we recently turned to our interest in microorganism co-culture in order to obtain new bioactive compounds. After analyzing the high-performance liquid chromatography (HPLC) profiles of the co-cultivation extracts of 616 strains of mangrove endophytic fungi and Acinetobacter johnsonii B2, together with their monoculture extracts, we found that the co-cultivation of Trichoderma sp.…”
Section: Introductionmentioning
confidence: 99%
“…In continuing the search for novel and bioactive natural products from mangrove endophytic fungi [ 17 , 18 , 19 , 20 ], we recently turned to our interest in microorganism co-culture in order to obtain new bioactive compounds. After analyzing the high-performance liquid chromatography (HPLC) profiles of the co-cultivation extracts of 616 strains of mangrove endophytic fungi and Acinetobacter johnsonii B2, together with their monoculture extracts, we found that the co-cultivation of Trichoderma sp.…”
Section: Introductionmentioning
confidence: 99%
“…The above spectroscopic features suggested that 1 belonged to the austin analogue [ 16 ], whose planar structure is similar to the 1,2-dihydro-acetoxydehydroaustin B. However, the carbon chemical shifts values of C-1 (δ C 37.1) and C-2 (δ C 64.8) were different from those of 1,2-dihydro-acetoxydehydroaustin B.…”
Section: Resultsmentioning
confidence: 99%
“…Although meroterpenoids have a wide range of biological activities [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], few biological activities have been reported for austin and austin analogues. In this work, Compounds 1 – 10 were evaluated for their acetylcholinesterase (AChE) inhibitory activity using Huperzine A as a control ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations